ANALISA DRUG RELATED PROBLEMS (DRPs) PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RSUD DR HARJONO PONOROGO - Septiani, Dela Dwi; R.F.X Premihadi Putra; Susilowati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Chronic Kidney Disease (CKD) is a progressive condition that affects more than 10% of the world's population, with more than 800 million sufferers. Treatment for CKD includes conservative therapy and renal replacement therapy, such as transplantation. Management of comorbidities in CKD patients can increase the risk of Drug Related Problems (DRPs). This study aims to determine the characteristics of CKD patients, analyze kidney conditions based on Glomerular Filtration Rate (GFR), and identify the percentage of three categories of DRPs in hemodialysis patients at Dr. Harjono Ponorogo Hospital. The study was descriptive retrospective with purposive sampling technique based on inclusion and exclusion criteria. The results showed that the majority of patients were male (59.80%), aged 56-65 years (34.31%), and had comorbid renal anemia (82.35%). The largest GFR category was G5 (<15 mL/min/1.73 m²) at 92.16%. The percentage of DRPs includes overdose (0%), drug interactions (50%), and drugs for inappropriate indications (0%).